Polymer‐Templated Formation of Polydopamine‐Coated SnO2 Nanocrystals: Anodes for Cyclable Lithium‐Ion Batteries - Jiang, Beibei; He, Yanjie; Li, Bo; Zhao, Shiqiang; Wang, Shun; He, Yan‐Bing; Lin, Zhiqun (Angewandte Chemie International Edition, 2017)
Well‐controlled nanostructures and a high fraction of Sn/Li2O interface are critical to enhance the coulombic efficiency and cyclic performance of SnO2‐based electrodes for lithium‐ion batteries (LIBs). Polydopamine (PDA)‐coated SnO2 nanocrystals, composed of hundreds of PDA‐coated “corn‐like” SnO2 nanoparticles (diameter ca. 5 nm) decorated along a “cob”, addressed the irreversibility issue of SnO2‐based electrodes. The PDA‐coated SnO2 were crafted by capitalizing on rationally designed bottlebrush‐like hydroxypropyl cellulose‐graft‐poly (acrylic acid) (HPC‐g‐PAA) as a template and was coated with PDA to construct a passivating solid‐electrolyte interphase (SEI) layer. In combination, the corn‐like nanostructure and the protective PDA coating contributed to a PDA‐coated SnO2 electrode with excellent rate capability, superior long‐term stability over 300 cycles, and high Sn→SnO2 reversibility. Corn‐on‐the‐cob: A porous electrode material comprising SnO2 nanocrystals coated with a protective polydopamine thin layer was prepared. The electrode exhibits excellent rate capability and long‐term stability for more than 300 cycles at test current densities from 160 to 1500 mA g−1. Sn→SnO2 reversibility was observed with capacities approaching the theoretical capacity of 1494 mA h g−1 at a low current density of 160 mA g−1.